Surface Roughness in Drilling of Electrically Conductive Polyamide - Uysal, A.; Altan, E. (POLISH ACAD SCIENCES INST PHYSICS, 2016)
In this study, drilling of unreinforced polyamide and carbon black reinforced electrically conductive polyamide was performed with drill tools having different drill point angle at different cutting speeds and feeds. The surface roughness of drilled holes was measured and the chip forms were investigated. The experimental studies were designed by utilizing Taguchi L-9 orthogonal series in order to obtain optimum drilling parameters and analysis of variance (ANOVA) statistical method was used to specify the effects of the process parameters on the surface roughness.
Keywords: COMPOSITES; POLYETHYLENE; Physics